2008
DOI: 10.1007/s10508-008-9418-x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Milestones and Factors Associated with Coitus Initiation Among Israeli High School Students

Abstract: In view of the developmental approach to sexual behavior, this article presents the stages of sexual behavior leading to coitus in four grades of high school students in Israel and the sociodemographic factors associated with initiating coitus. Analyses were based on data from the first national study dealing comprehensively with sexuality in 30 years. A self-administered questionnaire was completed by a random sample of 4,609 students of the General Educational (secular) system that included 68% of the Hebrew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Earlier studies have shown that romantic timetables of Israeli adolescents resemble those of American adolescents (Carver et al 2003;Shulman and Scharf 2000). Despite these similarities, there are also findings that suggest different sexual behavior trajectories may exist among males and females from different cultures (Shtarkshall et al 2009). This study, however, also has many strengths.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies have shown that romantic timetables of Israeli adolescents resemble those of American adolescents (Carver et al 2003;Shulman and Scharf 2000). Despite these similarities, there are also findings that suggest different sexual behavior trajectories may exist among males and females from different cultures (Shtarkshall et al 2009). This study, however, also has many strengths.…”
Section: Discussionmentioning
confidence: 97%
“…Men tend to initiate sex earlier while women tend to initiate sex later (Teitler 2002). Similarly, in their discussion of their findings, Shtarkshall et al (2009) suggest that girls perceived themselves as different from the boys, possibly lending legitimacy to them to postpone coitus.…”
Section: Introductionmentioning
confidence: 91%
“…Former findings suggest that females are at increased risk for depression when sexual behavior takes place within a non stable relationship (Grello et al 2003). Considering the different sexual trajectories in sexual behavior for Israeli adolescent males and females with females reporting lower sexual involvement (Shtarkshall et al 2009),we also hypothesized that the association between sexual behavior and depressive affect in short-term relationships would be more pronounced among adolescent females than adolescent males.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations